Periapical lesions decrease insulin signaling in rat skeletal muscle - Astolphi, Rafael Dias [UNESP]; Curbete, Mariane Machado [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Ervolino, Edilson [UNESP]; Mota, Max Sander de Oliveira da[UNESP]; Antoniali, Cristina [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Sumida, Doris Hissako [UNESP] (Elsevier B. V., 2015)
Serum inflammatory cytokines derived from oral inflammation are associated with decreased insulin signaling (IS) and insulin resistance, which is a major risk factor for type 2 diabetes mellitus. This study aimed to investigate IS in the liver and skeletal muscle (SM) and disorders related to the serum lipid profile and glucose and insulin levels of nondiabetic rats with induced chronic periapical lesions (PLs). Twenty-eight Wistar rats were divided into control and PL groups. PLs were induced by exposing the pulpal tissue to the oral environment. Experiments were conducted in both groups 30 days after pulp exposure. Maxillae were processed for histopathological analysis. IS was evaluated according to insulin receptor substrate (pp185-insulin receptor substrate 1 [IRS-1]/insulin receptor substrate 2 [IRS-2]) tyrosine phosphorylation status, IRS-1 serine phosphorylation status, and IRS-1 and IRS-2 content in the liver and SM by Western blotting. Serum total cholesterol, triglyceride, glucose, and insulin levels were measured enzymatically using a commercial kit. PL rats showed reduced pp185 P-Tyr and increased IRS-1 serine phosphorylation status in the SM but no change in the liver after insulin stimulation. No significant changes in IRS-1 and IRS-2 content, serum total cholesterol, triglyceride, glucose or insulin levels were noted. PLs are associated with decreased insulin signaling in the SM of rats. Because a decrease in insulin signaling is associated with insulin resistance, our results emphasize the importance of preventing local inflammatory diseases such as PLs to prevent alterations in IS in muscle.
Keywords: Insulin receptor substrate proteins; Lipidemia; Periapical lesions; Skeletal muscle